Television in Europe - Coleman, James A.; Rollet, Brigitte (Intellect European studies series (Unnumbered), 1997)
Television in Europe draws out the distinctive features of European television by examining the history of each country's broadcasting, funding and ownership, public service ethics, key legislation, etc.